A prática pedagógica da educação física com a educação infantil: diálogos entre a sociologia da infância e o comportamento motor - Ewald, Anne Schneider (2021)
The Physical Education pedagogical practices with early childhood education, have been historically marked by approaches that offer little scope for the active participation of children during their learning and development processes. Such practices, influenced by biological and universal paradigms, whose emphasis lies on the maturational factors of the children 's development, is secondary to the socio-cultural dimension present in this process. Seeking to affirm pedagogical practices that take into consideration the children in all their biopsychosocial complexity, this essay aims at: a) analyzing a pedagogical mediation proposal of Physical Education with Children’s Education that has mobilized assumptions of the Children’s Sociology and Motor Behavior; and b) evaluating the mediation process undertaken, considering the Teacher’s pedagogical posture, the theoretical assumptions mobilized and, above all, the children’s ways of communicating and expressing themselves. The work uses the existential research-action as methodological option, which was held at a Children’s Education Municipal Center in the city of Vitória/ES, with a group of twelve children from five to six years old. The research lasted for six months, in a total of 40 meetings, which had themes of games and playful activities with the sports. Data was produced through the participant observation, drawings and picturesthat had been systematized into a field diary. The mediations were built in a dialogic relation, in partnership between Teachers and children, and the performance of the motor skills had not been oriented from the outside, however it happened through a process that considered the child’s agencies and their subjectivities. The diversification and the combination of the abilities to run, hop, dribble, throw, bounce, receive and manipulate materials make sense to the children, once they have been carried out on the basis of their experiences and before their copyright practices. Based on the interpretative reproduction, children implemented their identity marks on the cultural goods that they have have been introduced to, giving a new meaning according to their interests and possibilities. By anchoring on the assumption of the Motor Learning, it was played a fun activity in which the children were free to decide how to perform their motorskills during open and closed situations. These decisions demanded parametric adaptations that happened as long as the disorders were included. The Teacher has developed the sensitive listening and the watchful eye towards the different languages of the children, the singular ways of expressing themselves and communicating. By giving a new meaning to the view on the Motor Behaviour field, it was taken into consideration the children’s individualities, the socio cultural context in which the 13 children are develop and the singular way they act and communicate. The pedagogical practices analyzed indicated possibilities to mobilyze the assumptions of the Motor Behavior and the Children’s Sociology, contributing for the effectiveness of mediationsthat consider the children as active subjects in their own development process. The work highlighted the necessity of more research to address the school daily life and that the scientific knowledge production is each time closer to what really happens regarding pedagogical practice with young children, overcoming, this way, the dichotomy between theory and practice.